Substandard Reinforced Concrete Walls with Rectangular Cross-section: Assessment of Shear Resistance - Moretti, Marina (Technical Annals, 2024)
Reinforced concrete walls in buildings constructed prior to 1990 possess low shear resistance and their reinforcement detailing differs considerably as compared to similar walls in modern buildings, designed according to modern code principles. For the seismic capacity assessment of older buildings the correct estimation of shear resistance of existing RC walls is crucial. In previous research it has been demonstrated that available design models are not capable of reliably predicting the shear resistance of RC walls with reinforcement different than the one prescribed by modern codes. In this paper, a design model is presented for the assessment of shear resistance of RC walls with rectangular section, irrespective of reinforcement configuration. The model includes the contribution of all major mechanisms to shear resistance, namely: the longitudinal reinforcement of the confined regions at either end of the cross-section, the horizontal and vertical web reinforcement, the axial compressive force, and the concrete strut. The proposed equations have no restrictions in their applicability, in contrast to the majority of existing models, and proved to be the most effective in assessing the shear resistance of 129 tested RC walls, among 14 other design models considered, including existing design codes. Indicative examples are provided to demonstrate the better predictive capacity of the proposed equations.